Signatures of selection and candidate genes for adaptation to extreme environmental factors in the genomes of Turano-Mongolian cattle breeds - N. S. Yudin; A. A. Yurchenko; D. M. Larkin (Вавиловский журнал генетики и селекции)
Changes in the environment force populations of organisms to adapt to new conditions, either through phenotypic plasticity or through genetic or epigenetic changes. Signatures of selection, such as specific changes in the frequency of alleles and haplotypes, as well as the reduction or increase in genetic diversity, help to identify changes in the cattle genome in response to natural and artificial selection, as well as loci and genetic variants directly affecting adaptive and economically important traits. Advances in genetics and biotechnology enable a rapid transfer of unique genetic variants that have originated in local cattle breeds in the process of adaptation to local environments into the genomes of cosmopolitan high-performance breeds, in order to preserve their outstanding performance in new environments. It is also possible to use genomic selection approach to increase the frequency of already present adaptive alleles in cosmopolitan breeds. The review examines recent work on the origin and evolution of Turano-Mongolian cattle breeds, adaptation of Turano-Mongolian cattle to extreme environments, and summarizes available information on potential candidate genes for climate adaptation of Turano-Mongolian breeds, including cold resistance genes, immune response genes, and high-altitude adaptation genes. The authors conclude that the current literature data do not provide preference to one of the two possible scenarios of Turano-Mongolian breed origins: as a result of the domestication of a wild aurochs at East Asia or as a result of the migration of taurine proto-population from the Middle East. Turano-Mongolian breeds show a high degree of adaptation to extreme climatic conditions (cold, heat, lack of oxygen in the highlands) and parasites (mosquitoes, ticks, bacterial and viral infections). As a result of high-density genotyping and sequencing of genomes and transcriptomes, prospective candidate genes and genetic variants involved in adaptation to environmental factors have recently been identified.